Conservation and diversification of HAIRY MERISTEM gene family in land plants. (27th March 2021) - Geng, Yuan; Guo, Lei; Han, Han; Liu, Xing; Banks, Jo Ann; Wisecaver, Jennifer H.; Zhou, Yun
SUMMARY: The shoot apical meristems (SAMs) of land plants are crucial for plant growth and organ formation. In several angiosperms, the HAIRY MERISTEM ( HAM ) genes function as key regulators that control meristem development and stem cell homeostasis. To date, the origin and evolutionary history of the HAM family in land plants remains unclear. Potentially shared and divergent functions of HAM family members from angiosperms and non‐angiosperms are also not known. In constructing a comprehensive phylogeny of the HAM family, we show that HAM proteins are widely present in land plants and that HAM proteins originated prior to the divergence of bryophytes. The HAM family was duplicated in a common ancestor of angiosperms, leading to two distinct groups: type I and type II. Type‐II HAM members are widely present in angiosperms, whereas type‐I HAM members were independently lost in different orders of monocots. Furthermore, HAM members from angiosperms and non‐angiosperms (including bryophytes, lycophytes, ferns and gymnosperms) are able to replace the role of the type‐II HAM genes in Arabidopsis, maintaining established SAMs and promoting the initiation of new stem cell niches. Our results uncover the conserved functions of HAM family members and reveal the conserved regulatory mechanisms underlying HAM expression patterning in meristems, providing insight into the evolution of key stem cell regulators in land plants. Significance Statement: Meristems are crucial for organ development and plant architecture, and therefore how the key meristem regulators originated and evolved in land plants is an important question. In this work, we uncovered the mechanisms underlying the innovation, conservation and diversification of the HAM family – an important family of meristem regulators – in land plants.